PROFESIONALISME KERJA TERHADAP PENINGKATAN KUALITAS PELAYANAN PUBLIK DESA BARINGIN KECAMATAN MAIWA KABUPATEN ENREKANG - Miranda; Muhammad Ikbal; Hardianti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Miranda, 2025. Work Professionalism on Improving the Quality of Public Services in Baringin Village, Maiwa District,Enrekang Regency,supervised by Mr. Muhammad Ikbal and Mrs. Hardianti. This study aims to determine professionalism and the quality of public services in Baringin Village, and the influence of work professionalism on improving the quality of public services in Baringin Village. This study used a quantitative descriptive approach with 72 sumber datats using a random sampling technique. Data were collected through observation, questionnaires, and literature review, then analyzed using IBM SPSS Statistics 21.0. The results of the study indicate that work professionalism at the Baringin Village Office is categorized as good, with the following percentages: a) Ability 67.2%, b) Quality 63.8%, c) Facilities 59.4%, d) Infrastructure 65.2%, e) Human resources 61.2%, f) Technology 63.6%, g) Reliability 62.2%. Meanwhile, service quality at the Baringin Village Office is categorized as quite good, with the following percentages: a) Physical evidence 65.4%, b) Reliability 60.2%, c) Responsiveness 59.4%, d) Assurance 61.8%, e) Empathy 56.6%. Based on the results of the simple linear regression test, the F-value > F-table (6.485 > 0.227), so it can be concluded that work professionalism has quite an influence on the quality of public services in Baringin Village, Maiwa District, Enrekang Regency. Keywords: Work professionalism, Service quality